(untitled) (Journal of Interdisciplinary Insights, 2023)
The formulation of a country’s grand strategy and neighborhood diplomatic strategy is predicated upon the strategic environment in which great powers are emerging. The diplomatic approach concerning China and India is significantly shaped and constrained by its strategic context, encompassing both external and internal factors. This context is manifested through the assessment of the global situation and the understanding of the domestic environment. This study aims to analyze and evaluate the diplomatic strategic environments surrounding China and India, focusing on three key aspects: geographical environment, rival environment, and internal environment. Through deconstructing these environments, we will identify both the similarities and contrasts between the two countries. Based on an analysis of the geographical and diplomatic strategies of China and India, it can be observed that both countries own both land and sea territories, thereby exhibiting a dual nature encompassing both oceanic and terrestrial domains. However, it is noteworthy that India’s surrounding nations are limited in number and comparatively less influential, so endowing India with a substantially superior geo-environmental position. Based on an analysis of the respective international environments, it can be observed that both China and India encounter similar challenges. However, China is presented with more pronounced geopolitical counter-measures. This discrepancy in the level of counter-measures may be attributed to the distinction between the current circumstances and future prospects in facing a shared strategic opponent environment. The internal environments of both countries exhibit distinct developmental strengths and advantages. However, it is worth noting that China has achieved a higher stage of development compared to India, and its developmental trajectory appears to be more promising.